Analytical quality by design aided RP-HPLC method for the estimation of sunset yellow in commercial food samples employing green ultrasound assisted extraction: Greenness, blueness and whiteness evaluation - Atyurmila Chakraborty; Kavitha Jayaseelan (Green Analytical Chemistry)
Sunset Yellow FCF (E110) is a widely utillized azo synthetic food colorant due to its appealing hue and significant market popularity. Attributable to the health risks caused by excessive usage of Sunset Yellow, ecologically safe method for quantifying the same are to be prioritized. The purpose of this study is to develop and validate an Analytical Quality by Design based eco-friendly HPLC method followed by ultrasound assisted extraction of food samples and confirmation of them using FTIR. To comply with the requirements of green analytical chemistry ethanol was utilized because of its environmental friendliness nature. The chromatographic parameters were optimized using rotatable central composite designs (rCCD) whereas the separation was performed on a Phenomenex column (C18, 250 mm × 4.6 mm, i.d 5 μm) using a mobile phase consisting of a 34.4:65.6 (v/v) mixture of ethanol and acetate buffer at flow rate of 1.1 ml/min with detection wavelength of 510 nm. The elution of Sunset Yellow occurred after 2.133 min. The method was thoroughly validated and tested as part of the forced degradation investigation to ascertain its stability-indicating properties. When evaluating the extent of greenness, the Green Analytical Procedure Index, Analytical Eco Scale and AGREE metrics tools yielded the best findings. The blueness and whiteness of the method was assessed by Blue Applicability Grade Index and Red-Green-Blue 12 (RGB 12) algorithm respectively with a high score which shows high practicality, cost effectiveness and ecofriendliness of the method.